Histopathologic evaluation of saphenous vein grafts in patients with type II diabetes mellitus undergoing coronary artery bypass grafting - AK, ESİN; AK, KORAY; ARSAN, SİNAN; ÇETİNEL, ŞULE (ELSEVIER SCIENCE INC, 2021)
Introduction: Diabetes Mellitus (DM) has been known to be a risk factor for the development of more severe form of saphenous vein graft disease after coronary artery bypass grafting (CABG). We aimed to evaluate the impact of type II-DM on histopathological features of great saphenous vein grafts of patients undergoing CABG. Patients and methods: Forty consecutive patients undergoing elective CABG were enrolled into the study. Patients were grouped into two; Diabetic group (n = 20); includes patients with preoperative diagnosis of type II-DM and Nondiabetic group (n = 20): those without type II-DM. In all patients, a short segment of the great saphenous vein graft at the level of medial malleolus was taken for light microscopy and transmission electron microscopy (TEM) evaluation. Moreover, immunoexpressions of Caveolin-1, Vascular cell adhesion protein 1 (VCAM-1) and endothelial nitric oxide synthase (eNOS) were studied. Results: There were no differences in the demographics of patients between two groups. The magnitude of intimal fibrosis in diabetic group was slightly higher than in nondiabetics (1.95 +/- 0.99 versus 1.3 +/- 0.8, P = .04). In TEM, vacuolization in endothelial cells, substance accumulation along with coarse collagen fibers and cytoplasmic degeneration with vacuolization in muscle cells were detected in diabetic group. While there were no differences in Caveolin-1 and VCAM-1 immunostaining, the intensity of positive eNOS immunostaining was significantly higher in endothelium (2.10 +/- 0.64 versus 1.55 +/- 0.68, P = .01) and tunica media 1.75 +/- 0.63 versus 1.2 +/- 0.52, P = .007) in nondiabetic group, respectively) compared with diabetic group. Conclusion: Type II DM might be a reason for decreased expression of eNOS and increased intimal fibrosis, vacuolization of endothelial and smooth muscle cells in saphenous vein grafts. The clinical implications of these alterations on the graft patency need to be evaluated. (c) 2021 Elsevier Inc. All rights reserved.
Keywords: Type II Diabetes Mellitus; great saphenous vein; histopathology; immunohistochemistry; Caveolin-1; eNOS and VCAM-1; SMOOTH-MUSCLE-CELLS; ADHESION MOLECULES; PATHOGENESIS; HYPERPLASIA; EXPRESSION; PATENCY; SURGERY; MATRIX